2019
DOI: 10.1080/17515831.2019.1569852
|View full text |Cite
|
Sign up to set email alerts
|

Tribological studies of automotive piston ring by diamond-like carbon coating

Abstract: Increasing environmental awareness and demanding low energy consumption are of the top priorities for future vehicles manufacturing companies. This can be achieved by reducing wear and friction of engine components, so that its efficiency and lifetime can be increased. Surface treatments and coatings contribute to a better lubrication with oils and can participate significantly in achieving these goals. In this paper, diamond-like carbon (DLC) coating has been incorporated to the vehicle piston rings with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is very important that the coatings have a low coefficient of friction. Because the high coefficient of friction increases the wear rate that affects the performance of the engine (Vinoth et al, 2019). For this reason, it is necessary to know the effects of surface coatings applied to the rings against friction.…”
Section: Introductionmentioning
confidence: 99%
“…It is very important that the coatings have a low coefficient of friction. Because the high coefficient of friction increases the wear rate that affects the performance of the engine (Vinoth et al, 2019). For this reason, it is necessary to know the effects of surface coatings applied to the rings against friction.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of traditional ceramic coatings with a hard, low-friction surface has been shown to work well for anti-wear coatings, and amorphous carbon has been shown to improve the frictional strength of the chrome surface. In [44], it was shown that a diamond-like carbon (DLC) coating shows smaller wear and friction under operating conditions similar to those of uncoated piston rings. Thus, it has been proven that the use of a DLC coating contributes to an increase in the service life of the piston elements in internal combustion engines.…”
Section: Introductionmentioning
confidence: 99%
“…The coatings deposited with various thermal spray variants, i.e. WC–Cr 3 C 2 –Ni [1], WC [3], WC–Co [4], WC–NiCr [5] and WC–CoCr [6,7] could be employed for brake pistons [8], gears [9], shock absorber rods [8] and engine components [3,10]. The primary tribological design objective of gear life is higher resistance to abrasive wear, erosion wear and corrosion.…”
Section: Introductionmentioning
confidence: 99%